ZnSe Modified Zinc Metal Anodes: Toward Enhanced Zincophilicity and Ionic Diffusion. Issue 35 (18th July 2021) - Li, Tian Chen; Lim, Yew Von; Xie, Xuesong; Li, Xue Liang; Li, Guojing; Fang, Daliang; Li, Yifan; Ang, Yee Sin; Ang, Lay Kee; Yang, Hui Ying
Abstract: Zinc metal is an ideal candidate for aqueous rechargeable batteries due to its high theoretical capacity and natural abundance. However, its commercialization is inevitably challenged by several critical factors such as dendrite growth and parasitic side‐reactions, leading to low coulombic efficiency and a limited lifespan. Herein, a modified Zn foil with a zincophilic ZnSe layer deposited by a simple selenization process is proposed. An order of magnitude stronger adsorption capability toward Zn 2+ ions and uniform ion diffusion tunnels of ZnSe enables lower nucleation energy barrier and faster ion‐diffusion kinetics. Meanwhile, detrimental Zn corrosion in aqueous system is also effectively mitigated. As a result, ZnSe@Zn anode shows reversible Zn plating/stripping (1700 h at 1 mA cm −2 ) with ultra‐low voltage hysteresis (41 mV), contributing to exceptional cycling stability over 500 cycles with negligible capacity fading for the ZnSe@Zn/MnO2 full cell. Abstract : A uniform multi‐functional ZnSe layer is constructed on Zn surface via a simple and facile selenization reaction. An order of magnitude stronger adsorption capability toward zinc ions and uniform ion diffusion tunnels of ZnSe enables lower nucleation energy barrier and faster ion‐diffusion kinetics, leading to superior cycling stability over 500 cycles with negligible capacity fading.